THE ANALYSIS OF FIGURATIVE LANGUAGE USED IN THE LYRIC OF AWAKEN BY MAHER ZAIN - Syifa Nuraeni; Taufik Ismail; Evie Kareviati (IKIP Siliwangi, 2020)
Figurative language is a part of semantic. This research analyzed the figurative language used in the lyric of Awaken by Maher Zain. The aims of this research are to figure out the figurative languages used in the lyric of Awaken and to analyze the contextual meaning of figurative language used in that song lyric. It is expected the result of this research will be useful for the reader especially in describing what figurative language is and what kinds of figurative language are. The design of this research is descriptive qualitative research. The lyrics of song is got from kapanlagi.com entitle Awaken. The result found that there are some kinds of figurative language used in Maher Zain’s song entitle Awaken, such as hyperbole, rhetoric, repetition and personification. The contextual meaning of each figurative language is also clarified. The conclusion of this research is there are some kinds of figurative language use by Maher Zain in his song entitle Awaken.